2019
DOI: 10.1161/circulationaha.118.037615
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Electromechanical Remodeling Following 2 Years of High-Intensity Exercise Training in Sedentary Middle-Aged Adults

Abstract: Background: Moderate intensity exercise is associated with a decreased incidence of atrial fibrillation. However, extensive training in competitive athletes is associated with an increased atrial fibrillation risk. We evaluated the effects of 24 months of high intensity exercise training on left atrial (LA) mechanical and electric remodeling in sedentary, healthy middle-aged adults. Methods: Sixty-one participants (53±5 years) were randomized to 10 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 54 publications
3
12
0
6
Order By: Relevance
“…A revisão da literatura resultou em 22 artigos, os quais foram classificados de acordo com o tipo de publicação: 8 coortes, 9,10,11,12,13,14,15,16 5 Ensaios clínicos, 17,18,19,20,29 3 Estudos caso-controle 21,22,23 e 6 Estudos observacionais. 24,25,26,27,28,30 .…”
Section: Resultsunclassified
“…A revisão da literatura resultou em 22 artigos, os quais foram classificados de acordo com o tipo de publicação: 8 coortes, 9,10,11,12,13,14,15,16 5 Ensaios clínicos, 17,18,19,20,29 3 Estudos caso-controle 21,22,23 e 6 Estudos observacionais. 24,25,26,27,28,30 .…”
Section: Resultsunclassified
“…However, BNP increased in our study despite the small BP reduction. It remains unknown whether long‐term IHG induces LA enlargement and increased BNP, although a previous study suggested that high‐intensity exercise training in the long term caused LA enlargement 10 …”
Section: Discussionmentioning
confidence: 99%
“…[76][77][78][79] In one study, 2 years of high-intensity exercise training in sedentary, healthy, middle-aged adults was associated with LA mechanical remodeling without electrical remodeling significantly in excess of LV remodeling, which is known to occur in the earlier stages of endurance training. 80 The differential mechanisms that drive pathologic remodeling at the atrial level from excessive training in athletes and pressure-volume overload of HFpEF remain unclear.…”
Section: Lifestyle Interventionsmentioning
confidence: 99%